Clinical Spectrum of Recurrent Urinary Tract Infections in Children: Recurrent Urinary Tract Infections in Children - Wani, Asma; Ashraf, Mohd; Wani, Nisar Ahmed; Naik, Suhail Ahmed; Andrabi, Syed Ashiq Nisar; Sheikh, Waseem Shafi (Journal of Pediatric Nephrology, 2023)
Background and Aim: Urinary tract infection (UTI), is a common bacterial infection in pediatric group, can be easily diagnosed, but its recurrence can indicate underlying serious anatomical defects of the urogenital tract, leading to acute morbidity and chronic medical condition, such as hypertension and renal insufficiency. Objective: To know the clinical spectrum and the frequency of recurrent UTI among children visiting our hospital. Methods: This prospective study was conducted during the period from April 2020 to March 2021, in the department of pediatrics and pediatric nephrology, Governmental Medical College, Srinagar. All children aged between 6 months to 18 years presenting with a history of recurrent urinary tract were included in the study. A detailed history, relevant clinical examination, and the ultrasonography of kidney ureters and bladder (USG KUB) followed by voiding cystourethrography (VCUG), were carried out and subsequently analyzed. Results: A total of 38 patients with recurrent UTI were evaluated during one year. The commonest age group was 6 months to 2 years (68%), with female preponderance (F: M 3.2:1). Urine culture grew E. coli in 95% of patients, while USG abnormalities and the presence of vesicoureteral reflux (VUR) on voiding cystourethrography (VCUG) were seen in 14 patients (36%). Conclusion: Recurrent UTI are common between 6 months to 2 years, and E coli is the most common cause. Children with the past history of UTI seem more predisposed to have another E.coli-associated UTI.